Neo-Colonialism and Dependent Development in African Countries: A Critical Analysis of Nigeria's Neo-Colonial Status - Musa, Abdullahi Ahmed; Awudu, Angyu Daniel; Elijah, Emmanuel (Kashere Journal of Politics and International Relations, 2025)
This study critically examined Neo-colonialism and Dependent Development of African Countries. The need for the liberation of Nigeria from the shackles of neo-colonial status and its negative impacts on the socio-economic and political spheres of the country is germane. Nigeria has been in a neo-colonial trap since independence in 1960 like many other African countries with the active involvement of the elites. The study adopted the secondary source of data collection and analysis. The dependency theory was adopted as the framework for analysis due to its relevance in explaining today’s global imbalances. The imperial powers employ economic, financial and trade policies to dominate less developed countries like Nigeria. This has generated greater dependence of the state in different dimensions regarding economic, political and socio-cultural aspects, irrespective of the nation's wealth. Through the Britton Woods Institutions loan conditionality, the IMF and World Bank have kept Nigeria and other African countries in a debt cycle leading to a perpetual debt trap and their inability to govern their economies. The study recommended that the Nigerian leadership should promote internal measures to direct its economic systems out of the shackles of neo-colonialism and imbalance relationship through industrialization and internal political and economic policies outside those of the Britton woods institutions of World Bank and IMF.